Educational Value in Merantau Culture of Indonesian Minangkabau Ethnic. - Ismira, Ismira; Ahman, Ahman; Supriatna, Mamat (Psikopedagogia, 2018)
The present study was aimed at discovering the educational values of Minangkabau Ethnic's merantau culture to be used as educational content, particularly in Career Guidance and Counseling. The educational values were dug from various "petatah petitih and pantoums of Minangkabau Ethnic" which affecting the Minangkabaunese perantau such as mindset, attitude, and behavior. The present study employed qualitative approach with ethnographic realism by exploring the wisdom of Merantau of Minangkabau Ethnic. The data were collected through interview with the culture figure and literature study. The finding of the study showed that in Minangkabau's Merantau Culture, there are four educational values namely the value of career success, knowledge and experiences, mental and social resilience, and the value of life skill. The finding of the study can be used as a reference in guidance and counseling to develop a local wisdom-based program.